2006
DOI: 10.1093/geronb/61.6.p333
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Forgetful and Slow Employees: Does Age Matter?

Abstract: Participants (perceivers) read a vignette describing a young or older employee (target) in a young-relevant or old-relevant work context who is either forgetful or slow. Regardless of work context, perceivers attributed older targets' forgetful and slow behavior more to internal stable causes but the identical behavior of younger targets more to internal unstable causes. Perceivers also felt less anger and greater sympathy and were more likely to recommend a promotion and raise for older than for young targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Participants based this leniency on the assumption that older adults were forgetful. Similarly, when people rated a slow worker, they viewed an older employee more favorably because they attributed the behavior to uncontrollable consequences of aging, whereas they viewed a younger worker more harshly (Erber & Long, 2006). Furthermore, social partners may not confront an older adult because they believe the older adult is intractable and will not change (Fingerman, 2003; Miller et al, 2009).…”
Section: Reasons Underlying Preferential Treatment Of Older Adultsmentioning
confidence: 99%
“…Participants based this leniency on the assumption that older adults were forgetful. Similarly, when people rated a slow worker, they viewed an older employee more favorably because they attributed the behavior to uncontrollable consequences of aging, whereas they viewed a younger worker more harshly (Erber & Long, 2006). Furthermore, social partners may not confront an older adult because they believe the older adult is intractable and will not change (Fingerman, 2003; Miller et al, 2009).…”
Section: Reasons Underlying Preferential Treatment Of Older Adultsmentioning
confidence: 99%
“…Although previous studies found significant effects of social stereotype on moral judgment (e.g., Blanchard-Fields et al, 1999; Erber & Long, 2006), most of these studies used ambiguous moral scenarios in which the perpetrator’s intention was unclear. For example, it was unclear whether an employee’s poor work performance was due to poor memory or negligence (Erber & long, 2006). In such ambiguous situations, social stereotypes are highly likely to bias people’s appraisal of the moral situation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, people are more forgiving of old perpetrators than young perpetrators in social transgressions (Miller, Charles, & Fingerman, 2009). In addition, people tend to attribute old adults’ misconduct to age-related decline in cognitive functioning but attribute young adults’ misconduct to hostile intention or negligence (Blanchard-Fields, Baldi, & Stein, 1999; Erber & Long, 2006). Although previous studies found that female perpetrators tend to be judged more leniently than male perpetrators in child sexual abuse scenarios (McCoy & Gray, 2007; Quas, Bottoms, Haegerich, & Nysse-Carris, 2002), the effect of the perpetrator’s gender was seldom investigated in other moral contexts.…”
mentioning
confidence: 99%
“…Speed of information processing is a fundamental property of cognitive agents and an important prerequisite for timely and adequate responses in complex environments. Older people are often assumed to be slower thinkers than younger people -a notion that has significant consequences in work life [1,2] and that has seemingly found strong empirical support. Over the past decades, a large body of research has consistently reported a negative relation between processing speed and age, that is, older people tend to be slower than younger people across a wide variety of cognitive tasks and contexts [3,4].…”
Section: Introductionmentioning
confidence: 99%